Energy versus Electron Transfer: Controlling the Excitation Transfer in Molecular Triads. Issue 20 (23rd March 2017) - Luo, Yusen; Barthelmes, Kevin; Wächtler, Maria; Winter, Andreas; Schubert, Ulrich S.; Dietzek, Benjamin
Abstract: The photochemistry of Ru II coordination compounds is generally discussed to originate from the lowest lying triplet metal‐to‐ligand charge‐transfer state ( 3 MLCT). However, when heteroleptic complexes are considered, for example, in the design of molecular triads for efficient photoinduced charge separation, a complex structure of 1 MLCT states, which can be populated in a rather narrow spectral window (typically around 450 nm) is to be considered. In this contribution we show that the localization of MLCT excited states on different ligands can affect the following ps to ns decay pathways to an extent that by tuning the excitation wavelength, intermolecular energy transfer from a Ru II –terpyridine unit to a fullerene acceptor can be favored over electron transfer within the molecular triad. These results might have important implications for the design of molecular dyads, triads, pentads and so forth with respect to a specifically targeted response of these complexes to photoexcitation. Abstract : Different light, different path : A molecular triadPTRuC60 containing a phenothiazine donor, Ru–terpyridine photocenter and a fullerene (electron and energy) acceptor displays distinct yet coexisting decay pathways (electron transfer and energy transfer). Herein, we show that the ratio between the two decay channels can be controlled by changing the excitation wavelength ( λ ex ), and is determined by the localization of metal‐to‐ligand charge transfer excited states on different ligands.